Improving the preservice teachers’ TPACK level through hybrid learning - Mega Wulandari; Annisa Agra Inggitajna (Journal of Applied Studies in Language, 2023)
This study aims to explore whether there is a significant improvement in preservice teachers’ Technological Pedagogical Content Knowledge (TPACK) after implementing hybrid presentation and teaching simulation as one of the tasks in the Teaching Methods and Conventional Media course. This study also reports students’ responses to the implementation of the hybrid presentation and teaching simulation. In this quantitative study, preservice teachers’ knowledge was measured using a TPACK scale prior to and subsequent to the hybrid class implementation period. Twenty-one students studying in the fourth semester of an English education department in a private university in Indonesia participated in this study. A paired-samples t-test result suggested a significant improvement in students’ scores from the pre- to the post- TPACK self-assessment (t = -8.210, p < .05). The findings of this study suggest that hybrid presentation can be an effective strategy to help foster preservice teachers’ TPACK skill while developing speaking and other skills.